Photo Noise. Issue 2 (2nd April 2016) - Kane, Carolyn L.
Abstract : Like past avant-garde movements, glitch and noise in the twenty-first century are used to reveal the materiality of the medium. But instead of providing insight or clarity into the politics or social conditions of a technology, they demarcate broader conditions of opacity and blockage, contributing to what Jodi Dean has called 'communicative capitalism'. The work of German photographer Thomas Ruff alongside the Düsseldorf School, New Photography and JPEG technology are used in this article to illustrate this tendency as a move away from meaning and toward visual noise and communicative breakdown. I use three core analytic registers: the deliberate failure to adhere to visual norms, communicative failure and machine failure and breakdown. Ruff's work uses visual noise as art to at once reaffirm pervasive conditions of breakdown, failure and decline in high-tech global capitalism, while simultaneously providing a temporary reprieve from these conditions through an emergent form of visual beauty.